Meningkatkan Personal Branding Mahasiswa melalui Public Speaking, Kredibilitas, dan Kecerdasan Emosional - Siahaan, Febri Sari; Rismanto, Caesar; Metris, Diksi; Restika, Dea; Muarief, Fahrurozi (CV. ITTC INDONESIA, 2025)
This study explores the relationship between public speaking, credibility, and emotional intelligence in shaping students' personal branding at Universitas Tangerang Raya. Using a quantitative approach with a correlational design, data were collected from 352 students through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SMART-PLS 4.0. The findings indicate that public speaking has a positive and significant impact on personal branding, both directly and through credibility as a mediator. Credibility plays a crucial role in enhancing audience trust and building a professional image. However, emotional intelligence does not moderate the relationship between public speaking and personal branding, suggesting that this factor does not strengthen or weaken the relationship within the study. These results highlight the importance of mastering public speaking skills for students to improve credibility and competitiveness in the job market. Furthermore, educational institutions are encouraged to provide communication skills training to support students' personal branding development. This study contributes to both academic understanding and practical applications in managing professional identity in today’s competitive landscape.